The Effects of Tetrabromobisphenol A (TBBPA) on the Mussel Mytilus galloprovincialis: A Multi-Biomarker Approach - Copeto, Sandra (2024)
Tetrabromobisphenol A (TBBPA) is a fire-retardant containing bromine, produced in large quantities worldwide and extensively used in several industrial products. This compound was identified as a potential contaminant of the environment, causing toxicity to organisms. However, its toxicity remains poorly understood in marine bivalves. The first objective of this work was to evaluate the impact of TBBPA on mussels (Mytilus galloprovincialis) exposed for 28 days to various concentrations of TBBPA (0, 1, 10, and 100 µg·L−1), by assessing stress biomarkers’ responses (Glutathione S-transferase, superoxide dismutase, catalase, lipid peroxidation, total antioxidant capacity, total ubiquitin, caspase-3 and acetylcholinesterase). The results showed that lower concentrations (1 and 10 µg·L−1) were efficiently detoxified, as suggested by GST activities, which were supported by the responses of the other biomarkers. The most pronounced effects were observed in animals exposed to the highest concentration of TBBPA (100 µg·L−1), suggesting oxidative stress. Additionally, significant strong correlations were found between total antioxidant capacity and some biomarkers (superoxide dismutase and lipid peroxidation), showing that processes involved in oxidative stress fighting are working to avoid cell injury. In brief, mussels’ defense mechanisms were capable of dealing with exposure to the lower concentrations tested. Despite this, the risk of consuming shellfish or other fishery products contaminated with TBBPA should be a cause for concern.